Characteristics of vertigo and the affected vestibular nerve systems in idiopathic bilateral vestibulopathy. (2nd January 2016) - Fujimoto, Chisato; Kinoshita, Makoto; Kamogashira, Teru; Egami, Naoya; Sugasawa, Keiko; Yamasoba, Tatsuya; Iwasaki, Shinichi
Abstract: Conclusion : Vertigo attacks in IBV patients involving both the superior and inferior vestibular nerve systems were significantly more severe than vertigo attacks in patients with selective involvement of the inferior vestibular nerve system alone. Objective : To investigate the relationship between the frequency and duration of vertigo and the affected vestibular nerve system in idiopathic bilateral vestibulopathy (IBV). Methods : This study categorized 44 IBV patients into the following three sub-groups according to the affected vestibular nerve system: superior, inferior, and mixed type. These patients were also categorized into the following three sub-groups according to their clinical time course: progressive type showing no episodes of vertigo, sequential type showing recurrent vertigo attacks and single-attack type showing a single episode of vertigo. Results : Ten, 11 and 23 patients were classified as the superior, the inferior, and the mixed type, respectively. Seventeen, 23, and four patients were classified as the progressive, the sequential, and the single-attack type, respectively. For the patients having one or more vertigo attacks, the duration of the vertigo attack was longer than 24 h in 69% of the mixed type, and the duration of vertigo in the mixed type was significantly longer than that in the inferior type ( p < 0.05).